Effect of second-order actions on the performance of resilient slip friction joints: Analytical and experimental investigation. (October 2021) - Mohamad Mahdi Yousef-beik, Seyed; Veismoradi, Sajad; Zarnani, Pouyan; Quenneville, Pierre
Abstract: The Resilient Slip Friction Joint (RSFJ) is a relatively new friction damper developed and introduced in New Zealand. It is used in structures to dissipate the earthquake energy with the advantage of re-centring the structure back to its upright position. This paper investigates the experimental and analytical behaviour of the RSFJ when it is affected by the second-order effect (SOE) both in the damper in-plane and out-of-plane cases due to possible inherent imperfection in reality. The main consequences of SOE is firstly the reduction of the axial force capacity, stiffness of the damper and in return the structure, change in damping ratio. All of these may end up changing the effective period and seismic response of the structure. The ultimate catastrophic effect of SOE might be the failure of the damper if it is not properly designed for it in advance. From this perspective, this paper proposes some analytical expressions for the prediction of the damper response when it is affected by SOE. Furthermore, it investigates the effect of boundary conditions on SOE and provides some recommendations so that the SOE is minimized.